1990
DOI: 10.1096/fasebj.4.14.2227213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology and biochemistry of pyruvate dehydrogenase complexes 1

Abstract: In most organisms, the pyruvate dehydrogenase complex catalyzes the pivotal irreversible reaction that leads to the consumption of glucose in the aerobic, energy-generating pathways. A combination of biochemical and molecular biology studies have greatly expanded our understanding of the overall structural organization of this multicomponent system, delineated the locations and elucidated the functions of structural domains of the catalytic components, and revealed significant evolutionary changes. Important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
434
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 587 publications
(441 citation statements)
references
References 0 publications
3
434
0
4
Order By: Relevance
“…Structurally, the active form of DLDH is a stable homodimer, with each monomer possessing a non-covalently but tightly bound FAD molecule, a transiently bound NAD + or NADH molecule, and a redox active center containing two cysteine residues (Cys-45 and Cys-50 in both human and rat) that are directly engaged in thiol-disulfide exchange reactions during catalysis (Brautigam, et al, 2005, Ciszak, et al, 2006, Thorpe and Williams, 1976, Williams, 1992. In vivo, DLDH oxidizes dihydrolipoamide that is covalently linked to acyltransferase using NAD + as the electron acceptor, leading to the release of NADH (Patel and Roche, 1990, Vettakkorumakankav and Patel, 1996, Williams, 1992. This reaction is usually referred to as the forward reaction of DLDH, as opposed to the reverse reaction, in which DLDH catalyzes the oxidation of NADH using lipoamide as the electron acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the active form of DLDH is a stable homodimer, with each monomer possessing a non-covalently but tightly bound FAD molecule, a transiently bound NAD + or NADH molecule, and a redox active center containing two cysteine residues (Cys-45 and Cys-50 in both human and rat) that are directly engaged in thiol-disulfide exchange reactions during catalysis (Brautigam, et al, 2005, Ciszak, et al, 2006, Thorpe and Williams, 1976, Williams, 1992. In vivo, DLDH oxidizes dihydrolipoamide that is covalently linked to acyltransferase using NAD + as the electron acceptor, leading to the release of NADH (Patel and Roche, 1990, Vettakkorumakankav and Patel, 1996, Williams, 1992. This reaction is usually referred to as the forward reaction of DLDH, as opposed to the reverse reaction, in which DLDH catalyzes the oxidation of NADH using lipoamide as the electron acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…PDC from eucaryotes comprises three catalytic components (El, E2, and E3) as well as component X essential to the E2 E3 interaction [1,2]. The E1 component catalyzes the rate-limiting reaction, namely, thiamine pyrophosphate (TPP)-dependent decarboxylation of pyruvate to produce 2-hydroxyethyl-TPP (HETPP) and reductive acetylation of lipoic acid residues covalently bound to E2.…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian E2 contains two distinct lipoyl domains (L1 and L2) located at the N-terminus [38,39]. It has been clearly demonstrated that the mammalian PDK binds to the internal lipoyl domain (L2), perhaps through a highly charged region at the C-terminus, and PDK binding requires the presence of the lipoyl prosthetic group [4,12,40].…”
Section: Discussionmentioning
confidence: 99%